2013
DOI: 10.1111/tid.12175
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and outcome of bloodstream infections during the pre‐engraftment phase in 521 allogeneic hematopoietic stem cell transplantations

Abstract: Background Bloodstream infection (BSI) after allogeneic hematopoietic stem cell transplantation (HSCT) is a well‐known complication during the pre‐engraftment phase. Knowledge of trends in etiology and antibiotic susceptibility of BSI is important as the time to effective antibiotic treatment is closely associated with survival in bacteremic patients with septic shock. Methods BSI during the pre‐engraftment phase was studied retrospectively in 521 patients undergoing HSCT at our center in 2001–2008. Incidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
80
2
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 20 publications
15
80
2
4
Order By: Relevance
“…90,91 In fact, in case of allogeneic HSCT, some types of donors, such as unrelated and cord blood, were associated with higher rate of BSI, probably because of longer pre-engraftment neutropenia, compared to peripheral blood as a stem source. 92 Male sex and advanced acute myeloid leukemia were found to increase the risk of BSIs in peripheral blood stem-cell transplantation in a large German study, while another cohort confirmed higher risk of BSI in case of acute leukemia and prolonged hospital stay, but found the opposite effect of the gender (higher BSI risk in females). 78,93 The presence of relapsed malignancy was also associated with an increased risk of bacteremia in a large study of pediatric cancer patients.…”
Section: Othersmentioning
confidence: 96%
“…90,91 In fact, in case of allogeneic HSCT, some types of donors, such as unrelated and cord blood, were associated with higher rate of BSI, probably because of longer pre-engraftment neutropenia, compared to peripheral blood as a stem source. 92 Male sex and advanced acute myeloid leukemia were found to increase the risk of BSIs in peripheral blood stem-cell transplantation in a large German study, while another cohort confirmed higher risk of BSI in case of acute leukemia and prolonged hospital stay, but found the opposite effect of the gender (higher BSI risk in females). 78,93 The presence of relapsed malignancy was also associated with an increased risk of bacteremia in a large study of pediatric cancer patients.…”
Section: Othersmentioning
confidence: 96%
“…27 As such, patients receiving RIC conditioning regimens typically have lower rates of BSI, likely due to decreased mucositis and shorter durations of neutropenia. 27,28 However, pediatric patients undergoing RIC transplant for non-malignant disease have been noted to have an increased BSI risk, 5 which may reflect the added risk for BSI associated with the underlying diagnosis itself (for example, primary immunodeficiency).…”
Section: Conditioning Regimenmentioning
confidence: 99%
“…Neutrophils and monocytes are the first cells to recover, closely followed by the NK cells. Consequently, during the first month after HSCT the patient is very susceptible to infections (33). …”
Section: Infectious Complicationsmentioning
confidence: 99%